Hayek on socialism and on the welfare state: A comment on Farrant and Mcphail's "Does F.A. Hayek's Road to Serfdom deserve to make a comeback?" - Bruce Caldwell (Duke University, Center for the History of Political Economy (CHOPE), 2010)
In a recent article in "Challenge" magazine, Andrew Farrant and Edward McPhail argue that the central message of F. A. Hayek's "The Road to Serfdom" is that any attempt to create a welfare state must lead inevitably to totalitarianism. I argue in my paper that this was not the central argument; that in his book Hayek was arguing against the dangers of socialist central planning, not the welfare state, and his argument was largely correct. In was only in later books, after the demise in the west of "hot socialism," that he took up the question of the dangers of the welfare state, and when he did so it was in more measured and gradualist terms.
Keywords: B2; B31; 330; Hayek; "The Road to Serfdom"; socialism; the welfare state; Paul Samuelson; Glenn Beck; planning; nationalization